1996
DOI: 10.1182/blood.v87.4.1282.bloodjournal8741282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fibroblast growth factor-4 (k-FGF) on long-term cultures of human bone marrow cells

Abstract: Fibroblast growth factor-4 (FGF-4), a highly mitogenic protein encoded by the k-fgf/hst oncogene, stimulates the growth of a variety of cells of mesenchymal and neuroectodermal origin. Addition of FGF-4 to human long-term bone marrow cultures increased both the cell density of the stromal layer and the number of hematopoietic colony forming cells in the cultures in a dose-dependent manner. Hematopoiesis in the stromal layer persisted for up to 8 months. Erythropoiesis was maintained for up to 4 weeks, but gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Several groups have investigated the effects of growth factors on marrow stromal cells. [39][40][41][42][43][44][45][46][47] Of note, BMSCs are a heterogeneous population of cells that reside in the postnatal bone marrow cavity in tight contact with Gronthos et al have demonstrated that, in the absence of serum, growth factors are required for the prolifera-and supporting the hematopoietic compartment. [25][26][27] They are clonogenic and are also referred to as colony-forming tion of BMSC in culture.…”
Section: Bmsc Fatementioning
confidence: 99%
“…Several groups have investigated the effects of growth factors on marrow stromal cells. [39][40][41][42][43][44][45][46][47] Of note, BMSCs are a heterogeneous population of cells that reside in the postnatal bone marrow cavity in tight contact with Gronthos et al have demonstrated that, in the absence of serum, growth factors are required for the prolifera-and supporting the hematopoietic compartment. [25][26][27] They are clonogenic and are also referred to as colony-forming tion of BMSC in culture.…”
Section: Bmsc Fatementioning
confidence: 99%
“…In cultures of normal long term bone marrow cells, TGF-b has been found to be a potent inhibitor of progenitor cell cycling and the addition of neutralising antibodies to TGF-b increases the percentage of progenitor cells in S phase (Eaves et al, 1991). In contrast, FGFs have been noted to signi®cantly enhance the progenitor content of long term bone marrow cultures Quito et al, 1996). These results indicate that one of the functions of bFGF in the hematopoietic environment may be to oppose or counterbalance the effects of TGF-b on hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Receptors for FGFs have been found on K562 cells (Allouche, 1995;Liuzzo and Moscatelli, 1996) and on CD34 hematopoietic progenitor cells (Berardi et al, 1995;Le Bousse-Kerdil Á es et al, 1996;Testa et al, 1996;Burger et al, 1998Burger et al, , 1999 and direct effects of bFGF have been shown on progenitor cell proliferation (Gabbianelli et al, 1990;Bruno et al, 1993;Gabrilove et al, 1994;Allouche, 1995;Berardi et al, 1995). These direct effects are signi®cantly less than those noted when bFGF is added to stromal based hematopoietic cultures Quito et al, 1996). It is possible that the effects of bFGF in stromal based cultures are signi®-cantly greater than direct effects on isolated progenitor cells, as one of the important functions of bFGF may be to oppose TGF-b which is produced in signi®cant quantities by bone marrow stromal cells (Eaves et al, 1991;Coetzee et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth factor requirement for the in vitro expansion of BMSCs has been investigated by several groups [28][29][30][31][32][33][34]. Gronthos and Simmons demonstrated that, in the absence of serum, growth factors are necessary for the proliferation of BMSCs in culture [29].…”
Section: Osteogenic Progenitors From Bmmentioning
confidence: 99%